Analisis Laporan Keuangan Berbasis Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah (SAK EMKM) Pada UMKM Di Kabupaten Tangerang - Maria Hulpa; Trisni Handayani (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the extent to which financial statements are implemented based on Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) used by MSMEs i Tangerang Ragency. This research is a descriptive qualitative research through observation, interviews and documentation. The research subject were the MSME owners selected in Tangerang Regency, namely Ali Lubis UMKM, Jaya Pancing UMKM, and Sayur Mayur UMKM. The type of data used is primary and secondary. Data analysis techniques use data reduction, data display and conclusion. The results of the study show that SMEs in Tangerang Regency have implemented SAK EMKM in it, but sre not fully in accordance with SAK EMKM. Constraints in the implementation of SAK EMKM –based financial reports are due to internal factors, namely lack of understanding, discipline and time constraints in preparing reports. While the external factors are because there is no supervision of the financial reports that business entities make and there is no socialization about SAK EMKM. Keywords: Financial Accounting, SAK EMKM, UMKM